Influencia de la humedad del suelo sobre la susceptibilidad de Brachiaria a hongos patógenos - Zúñiga Pereira, Cristhian; González Q., Roberto; Bustamante R., Elkin; Argel M., Pedro J. (1998)
The ability of four introductions of the genus Brachiaria to adapt to the influence of plant pathogenic fungi under two soil moisture regimes was evaluated. Pathogens limiting the development of the crop were determined and the frequency of occurrence indicated that Pythium, Rhizoctonia and Fusarium were the most important. The four introductions were inoculated with these fungi and evaluated under two soil moisture conditions: field capacity (CC) and saturation (SCC). The severity of the pathogen infection was evaluated with an established scale. The introductions CIAT 6780 and CIAT 16322 obtained a value of 3 on the scale which indicates that the plants died due to Rhizoctonia, Fusarium and Pythium, in saturated soil moisture conditions. The introduction CIAT 26110 showed symptoms, however these were not significant, whilst CIAT 6133 was unaffected by the pathogens in both of the moisture conditions.